THE ROLE OF CALDERA GEOPARK IN TOURISM DEVELOPMENT OF LAKE TOBA SUPER PRIORITY DESTINATIONS, INDONESIA - Bejo MULYADI; Sirojuzilam SIROJUZILAM; Suwardi LUBIS; Agus PURWOKO (Geo Journal of Tourism and Geosites)
This study aimed to analyze the role of the Toba Caldera Geopark as a mediating variable in the development of the Lake Toba area using the SEM-PLS data analysis technique. The research method using SEM-PLS analysis consists of submodels, namely measurement and structural models or external and internal models. The convergent validity of the PLS with reflective indicators is assessed based on the loading factors of the indicators. The results demonstrate that the Toba Caldera Geopark can accelerate the role of tourism variables such as attractions, amenities, and ancillaries in enhancing the development of the Lake Toba area. However, development has not increased the influence of tourism accessibility in the Lake Toba area. The integrated management of Caldera Geopark with tourism development is recommended as an effective approach to expedite the development of Lake Toba area. Tourist destinations were reported to significantly influence the development of the Lake Toba area, and the Caldera Toba Geopark mediated efforts to develop the tourism sector. Factors related to tourist destinations, such as attractions, amenities, and ancillaries, played a significant role in the development of the Lake Toba area. Accessibility did not have a significant influence on the development of the area, either directly or indirectly, through the Geopark. Development was required, including improving attractions, amenities, and ancillaries, using the Caldera Toba Geopark as an approach for management, utilization, and development. Collaboration between the government, private sector, and local and international communities creates sustainable tourism development programmes. Meanwhile, attention to environmental sustainability, local culture, and community participation was important for managing the UNESCO Global Geopark.